Matricellular Protein Periostin Promotes Pericyte Migration in Fibrotic Airways - Bignold, Rebecca E.; Johnson, Jill R. (Frontiers in Allergy, 2021)
Introduction: Periostin is a matricellular protein that is currently used as a biomarker for asthma. However, its contribution to tissue remodeling in allergic asthma is currently unknown. We have previously demonstrated that tissue-resident mesenchymal stem cells known as pericytes are a key cell type involved in airway remodeling. This is thought to be caused the uncoupling of pericytes from the microvasculature supporting the large airways, facilitated by inflammatory growth factors and cytokines. It is hypothesized that periostin may be produced by profibrotic pericytes and contribute to the remodeling observed in allergic asthma. Methods: Lung sections from mice with allergic airway disease driven by exposure to house dust mite (HDM) were stained using an anti-periostin antibody to explore its involvement in fibrotic lung disease. Human pericytes were cultured in vitro and stained for periostin to assess periostin expression. Migration assays were performed using human pericytes that were pretreated with TGF-β or periostin. ELISAs were also carried out to assess periostin expression levels in bronchoalveolar lavage fluid as well as the induction of periostin production by IL-13. Results: Immunostaining indicated that pericytes robustly express periostin, with increased expression following treatment with TGF-β. Migration assays demonstrated that pericytes treated with periostin were more migratory. Periostin production was also increased in HDM exposed mice as well as in cultured pericytes treated with IL-13. Conclusion: Periostin is produced by pericytes in response to TGF-β or IL-13, and periostin plays a key role in inducing pericyte migration. The increase in periostin expression in TGF-β or IL-13 treated pericytes suggests that IL-13 may trigger periostin production in pericytes whilst TGF-β modulates periostin expression to promote pericyte migration in the context of tissue fibrosis.